2018
DOI: 10.1371/journal.pone.0190556
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral effects of ketone body infusion with 3-hydroxybutyrate in humans: Reduced glucose uptake, unchanged oxygen consumption and increased blood flow by positron emission tomography. A randomized, controlled trial

Abstract: Ketone bodies are neuroprotective in neurological disorders such as epilepsy. We randomly studied nine healthy human subjects twice—with and without continuous infusion of 3-hydroxybutyrate–to define potential underlying mechanisms, assessed regionally (parietal, occipital, temporal, cortical grey, and frontal) by PET scan. During 3-hydroxybutyrate infusions concentrations increased to 5.5±0.4 mmol/l and cerebral glucose utilisation decreased 14%, oxygen consumption remained unchanged, and cerebral blood flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 41 publications
3
52
1
Order By: Relevance
“…Patient baseline characteristics and six-month outcome are summarized in Table 1. GCS on site was median 6 [3][4][5][6][7][8][9][10][11][12][13][14]. Two patients had type 2 diabetes.…”
Section: Patient Characteristics and Outcomementioning
confidence: 99%
See 3 more Smart Citations
“…Patient baseline characteristics and six-month outcome are summarized in Table 1. GCS on site was median 6 [3][4][5][6][7][8][9][10][11][12][13][14]. Two patients had type 2 diabetes.…”
Section: Patient Characteristics and Outcomementioning
confidence: 99%
“…Lactate/pyruvate ratio (27 [17-44] vs. 27 vs. 28 ), brain tissue PO 2 (29 [19-39] vs. 29.5 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] vs. 29 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] mm Hg) and ICP (10 [3-20] vs. 11 [5][6][7][8][9][10][11][12][13][14][15][16][17] (Figure 3(a)), representing a median 4.7-fold decrease of blood KB from fasting to stable nutrition state. Median individual plasma/brain KB ratio was 11.…”
Section: Modulation Of Cerebral Ketone Metabolism By Nutritional Statementioning
confidence: 99%
See 2 more Smart Citations
“…In the mitochondria 3-HB is also known to increase the expression of neurotrophic factor that facilitates respiration [14]. Very recently the study of healthy human subjects with and without continuous infusion of 3-HB demonstrated reduced cerebral glucose uptake and neuroprotective effects [15]. There is a striking similarity between the activity of polymer in bacteria and monomeric 3-HB in eukaryotic cells.…”
mentioning
confidence: 99%